2017
DOI: 10.5152/eurjrheum.2016.042
|View full text |Cite
|
Sign up to set email alerts
|

QT dispersion and P wave dispersion in patients with fibromyalgia

Abstract: Objective: Fibromyalgia (FM) is a chronic disease characterized by widespread pain. Somatic complaints associated with the cardiovascular system, such as chest pain and palpitations, are frequently seen in FM patients. P and QT dispersions are simple and inexpensive measurements reflecting the regional heterogeneity of atrial and ventricular repolarization, respectively. QT dispersion can cause serious ventricular arrhythmias. The aim of the present study was to evaluate QT dispersion and P wave dispersion in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Sarıfakıoğlu et al (11) have also showed that the risk of atrial fibrillation was increased in patients with FMS. In contrast to these data, Yolbas et al (13) reported similar frequencies of arrhythmias in patients with FMS when com- pared with controls. Likewise, we also found no significant correlation between EPS scores and clinical parameters.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Sarıfakıoğlu et al (11) have also showed that the risk of atrial fibrillation was increased in patients with FMS. In contrast to these data, Yolbas et al (13) reported similar frequencies of arrhythmias in patients with FMS when com- pared with controls. Likewise, we also found no significant correlation between EPS scores and clinical parameters.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast to these data, Kulshreshtha et al (12) reported that the autonomic reflex arc and cardiac autonomic function were normal in patients with FMS. Yolbas et al (13) also reported that long QT and P wave dispersions, which indirectly indicate atrial and/or ventricular arrhythmias, are seen in the patients with FMS with the same frequency as the controls.…”
Section: Introductionmentioning
confidence: 92%
“…Although there are studies evaluating the effects of FMS on cardiovascular function, there is a paucity of data about the electrical alterations of conduction that may predict atrial and/or ventricular arrhythmias in FMS patients [6,9,12]. To the best of our knowledge, this is the first study evaluating fQRS morphology and inter-and intraatrial EMD in addition to ventricular functions in FMS.…”
Section: Discussionmentioning
confidence: 98%
“…Impaired atrial conduction is an important step in the pathophysiology of AF. Atrial conduction times can be evaluated with both invasive (electrophysiological study) and noninvasive (Pd on ECG and atrial EMD on echocardiography) methods [12,14,32,33]. Recently, atrial EMD has been extensively used to predict the development of atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation